Cerebrospinal fluid concentrations of functionally important amino acids and metabolic compounds in patients with mild cognitive impairment and Alzheimer’s disease - Kaiser, Elmar; Schönknecht, Peter; Kaßner, Stefan Sebastian; Hildebrandt, Wulf; Kinscherf, Ralf; Schröder, Johannes (Neurodegenerative diseases, 2010)
Cerebrospinal fluid (CSF) biomarkers play an important role in the differential diagnosis of neurodegenerative diseases such as Alzheimer’s disease (AD) and its postulated precursor stage mild cognitive impairment (MCI). While CSF tau protein, phospho-tau protein and β-amyloid have become part of the diagnostic process in clinical routine, the importance of several other biomarkers remains quite unclear. Among these, amino acids and metabolic compounds have been studied in clinical conditions mostly other than AD and, to our knowledge, never in MCI. In patients with AD (n = 14) and MCI (n = 13) we now determined CSF levels of 36 different amino acids and metabolic compounds by high-performance liquid chromatography. We found that 8 out of 36 amino acids (urea, threonine, glutamate, citrulline, α-aminobutyric acid, ornithine, ammonia and arginine) were significantly elevated in the CSF of patients with AD compared to those with MCI. As most of these amino acids and metabolic compounds are functionally important for brain-specific metabolic processes, neurotransmitter pathways or compensatory mechanisms, our findings might reflect these changes occurring within the brain of patients with MCI and those who developed manifest AD.